2018
DOI: 10.3390/challe9010002
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Remaining Challenges in the Study of Influenza and Anthrax Infection in Lung Cell Culture

Abstract: For over 30 years, immortalized lung cells have enabled researchers to elucidate lung-pathogen molecular interactions. However, over the last five years, numerous commercial companies are now providing affordable, ready-to-use primary lung cells for use in research laboratories. Despite advances in primary cell culture, studies using immortalized lung cells still dominate the recent scientific literature. In this review, we highlight recent influenza and anthrax studies using in vitro primary lung tissue model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Although the H5N8 2.3.4.4B virus in 2016–2017 shows low transmissibility to humans, it is still necessary to see whether the H5N8/Seal‐2016 virus can adapt or be transmitted from seals to the human population. Despite the donor–donor variation which might result in heterogeneity of phenotypes in experimental outcomes, previous studies have shown that by using PCLS and ALI cultures without a recruitable immune system, each slice or ALI culture can be considered as a “mini” lung in certain circumstances, which provides an opportunity to study influenza infection from limited materials (Powell & Straub, 2018; W. Wu et al., 2010). In this case, the harbour seal cell cultures established in the present study should be a valuable tool because they reflect the real conditions and do not require live animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the H5N8 2.3.4.4B virus in 2016–2017 shows low transmissibility to humans, it is still necessary to see whether the H5N8/Seal‐2016 virus can adapt or be transmitted from seals to the human population. Despite the donor–donor variation which might result in heterogeneity of phenotypes in experimental outcomes, previous studies have shown that by using PCLS and ALI cultures without a recruitable immune system, each slice or ALI culture can be considered as a “mini” lung in certain circumstances, which provides an opportunity to study influenza infection from limited materials (Powell & Straub, 2018; W. Wu et al., 2010). In this case, the harbour seal cell cultures established in the present study should be a valuable tool because they reflect the real conditions and do not require live animals.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, based on the regional variability within the lung, the number of specific cells varies from slice to slice, which allows each PCLS to be justified as an individual “mini” lung (Liu et al., 2019). An alternative culture system is air–liquid interface (ALI) cultures (Powell & Straub, 2018). In this system, respiratory epithelial cells are isolated and grown on collagen‐coated filter supports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At ALI, the mucus readily forms about a week after air exposure and can shield the virus from escaping apically into the liquid medium. This forces the virus to travel laterally to the neighboring cell, similarly to the events occurred in a natural infection [12].…”
Section: Primary Human Tissue Culturementioning
confidence: 93%
“…The use of defined immortal cell lines that are readily infectable and in which influenza replicates is of obvious convenience. These systems contributed indeed significantly to our current understanding of influenza (reviewed in Powell et al, 2018Powell et al, ,2018). Nevertheless, established cell lines possess major disadvantages.…”
Section: Primary Human Tissue Culturementioning
confidence: 98%